The Impact of Real Factors and Inflation on the Performance of the U.S. Stock Market From 1960 to 1980: Discussion - Wachter, Susan M. (Journal of Finance, 1983)
Susan M. Wachter, The Impact of Real Factors and Inflation on the Performance of the U.S. Stock Market From 1960 to 1980: Discussion, The Journal of Finance, Vol. 38, No. 2, Papers and Proceedings Forty-First Annual Meeting American Finance Association New York, N.Y. December 28-30, 1982 (May, 1983), pp. 567-569